Enhancement of anti-murine colon cancer immunity by fusion of a SARS fragment to a low-immunogenic carcinoembryonic antigen - Lin, Chen-Si (BioMed Central, 2012)
BACKGROUND: It is widely understood that tumor cells express tumor-associated antigens (TAAs), of which many are usually in low immunogenicity; for example, carcinoembryonic antigen (CEA) is specifically expressed on human colon cancer cells and is viewed as a low-immunogenic TAA. How to activate host immunity against specific TAAs and to suppress tumor growth therefore becomes important in cancer therapy development. RESULTS: To enhance the immune efficiency of CEA in mice that received, we fused a partial CEA gene with exogenous SARS-CoV fragments. Oral vaccination of an attenuated Salmonella typhimurium strain transformed with plasmids encoding CEA-SARS-CoV fusion gene into BALB/c mice elicited significant increases in TNF-α and IL-10 in the serum. In addition, a smaller tumor volume was observed in CT26/CEA-bearing mice who received CEA-SARS-CoV gene therapy in comparison with those administered CEA alone. CONCLUSION: The administration of fusing CEA-SARS-CoV fragments may provide a promising strategy for strengthening the anti-tumor efficacy against low-immunogenic endogenous tumor antigens.